2013
DOI: 10.1128/jvi.01153-13
|View full text |Cite
|
Sign up to set email alerts
|

A Cholesterol Tag at the N Terminus of the Relatively Broad-Spectrum Fusion Inhibitory Peptide Targets an Earlier Stage of Fusion Glycoprotein Activation and Increases the Peptide's Antiviral Potency In Vivo

Abstract: In previous work, we designed peptides that showed potent inhibition of Newcastle disease virus (NDV) and infectious bronchitis virus (IBV) infections in chicken embryos. In this study, we demonstrate that peptides modified with cholesterol or 3 U of polyethylene glycol (PEG 3 ) conjugated to the peptides' N termini showed even more promising antiviral activities when tested in animal models. Both cholesterol-and cholesterol-PEG 3 -tagged peptides were able to protect chicken embryos from infection with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…The efficacy of N-terminally lipid conjugated fusion inhibitory peptides has been studied for both Ebola21and Newcastle Disease virus23. In the case of Newcastle Disease virus, Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of N-terminally lipid conjugated fusion inhibitory peptides has been studied for both Ebola21and Newcastle Disease virus23. In the case of Newcastle Disease virus, Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…Enterovirus A71 (EV-A71) strain BC08 , avian influenza virus (AIV) strain H9-WD (Wang et al, 2016b), canine distemper virus (CDV) strain MD77 (Lan et al, 2005), Newcastle disease virus (NDV) strain Lasota and infectious bronchitis virus (IBV) strain M41 (Li et al, 2013), porcine epidemic diarrhea virus (PEDV) strain CV777 (Sun et al, 2015), VSV strain Indiana (Wang et al, 2016a), HSV-1 strain F (Wang et al, 2011) and HCV strain JFH-1 (Xu et al, 2014) are reproduced in RD, MDCK, Vero, HeLa, Vero, HeLa, HEK293T, HeLa and Huh7.5.1 cells respectively, according to the reports indicated above. GFP-NDV strain NA-1 is generated by inserting an additional transcription cassette coding for the enhanced GFP between the P and M genes of the NDV genome (Wang et al, 2015).…”
Section: Virusesmentioning
confidence: 99%
“…We have established a concept for developing transfection vectors that may have wide applications in gene antiviral strategies, including the delivery of siRNA to combat viral infection. This approach has the potential to be utilized for the prevention and control of coronavirus PEDV [36]. However, our study demonstrates that the antiviral effect of dual shRNA-expressing plasmids was the same as single shRNA-N.…”
Section: Discussionmentioning
confidence: 76%
“…Coronavirus S glycoprotein shares a mechanism similar to other Class I virus glycoproteins for membrane fusion [15][16][17]. Our previous work has shown that the modi ed HR peptide e ciently blocks coronavirus infection [17,18].…”
Section: Introductionmentioning
confidence: 99%